1938
DOI: 10.1172/jci101003
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Diabetics to a Standard Test Dose of Insulin

Abstract: That some diabetics improve on high carbohydrate diets is an established fact (1, 2). The selection of suitable patients for this type of diet has, until the present, been one of trial and error. Recently MacBryde (3) has made an attempt to select cases on the basis of insulin sensitivity. He studied the response of a small group of diabetics to a standard test dose of insulin and concluded that they fell into two groups, the relatively insulin-resistant and the relatively insulinsensitive. The resistant group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1939
1939
1954
1954

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Proponents of the early use of glucose base their advocacy on the demonstration, in normal (10,11) and depancreatized (12,13) dogs, and in normal (7) and diabetic (3,9,14) human subjects, that hyperglycemia, all other things being equal, accelerates the peripheral oxidation of carbohydrate and the deposition of liver glycogen, thereby tending to suppress ketosis (6,7). The relevance of these observations for clinical diabetes has been established by Mirsky and his associates (9), who were able to stop severe diabetic ketosis by the administration of massive amounts of glucose alone.…”
Section: Introductionmentioning
confidence: 99%
“…Proponents of the early use of glucose base their advocacy on the demonstration, in normal (10,11) and depancreatized (12,13) dogs, and in normal (7) and diabetic (3,9,14) human subjects, that hyperglycemia, all other things being equal, accelerates the peripheral oxidation of carbohydrate and the deposition of liver glycogen, thereby tending to suppress ketosis (6,7). The relevance of these observations for clinical diabetes has been established by Mirsky and his associates (9), who were able to stop severe diabetic ketosis by the administration of massive amounts of glucose alone.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity to Insulin.-In an earlier review 1S attention was called to the contradiction between the conclusions of MacBryde,60 using a modification of the Radoslav61 procedure as a means of determining sensitivity to insulin, and those of Himsworth.62 The subject has received further study by Klatskin,63 as well as by Bürgert, Scott and Nadler. The authors claimed to have shown con¬ clusively that insulin is absorbed and active when given by mouth, according to the procedure described, but they reserved judgment as to the clinical usefulness of the preparation until it has received wider clinical trial.…”
Section: Homeostasis Of Blood Sugarmentioning
confidence: 99%